2019
DOI: 10.1016/j.conbuildmat.2019.07.110
|View full text |Cite
|
Sign up to set email alerts
|

Compressive strength assessment of recycled aggregate concrete using Schmidt rebound hammer and core testing

Abstract: The main objective of this study was to estimate the compressive strength of recycled aggregate concrete (RAC) by means of Schmidt rebound hammer and core testing. The use of recycled aggregate in concrete has been shown to lead to a decrease in the construction cost and it can reduce the burden on the environment by saving natural aggregates. On the other hand, some nondestructive and semi-destructive techniques, such as Schmidt rebound hammer and core testing, are long-established methods for strength estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 41 publications
(43 reference statements)
4
41
0
2
Order By: Relevance
“…The results given by Grieb [13] showed that the rebound number of concrete materials with a specific type of aggregate was different to that with the same type of aggregate, provided from another source, while the difference between the data of Schmidt hammer test at various locations of a concrete element was negligible as reported by Xu and Li [14]. In 2019, Kazemi et al [3] combined the results of Schmidt rebound hammer with the core testing method to estimate the compressive strength of a limited number of concrete samples made by the partial replacement of natural aggregates with recycled coarse aggregate (RCA). As per the results, there was a strong correlation between Schmidt rebound hammer and the core testing method to reliably estimate the in-situ strength of concrete.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results given by Grieb [13] showed that the rebound number of concrete materials with a specific type of aggregate was different to that with the same type of aggregate, provided from another source, while the difference between the data of Schmidt hammer test at various locations of a concrete element was negligible as reported by Xu and Li [14]. In 2019, Kazemi et al [3] combined the results of Schmidt rebound hammer with the core testing method to estimate the compressive strength of a limited number of concrete samples made by the partial replacement of natural aggregates with recycled coarse aggregate (RCA). As per the results, there was a strong correlation between Schmidt rebound hammer and the core testing method to reliably estimate the in-situ strength of concrete.…”
Section: Introductionmentioning
confidence: 98%
“…Over the last decade, the estimation of the in-situ strength of specific types of concrete materials such as recycled aggregate concrete has drawn much attention from researchers owing to the difference between the manufacturing conditions of existing concrete at the construction sites and those of standard samples in the laboratory. Therefore, partially and nondestructive testing methods have been proposed to estimate the on-site strength of concrete materials [1][2][3][4][5][6]. The point load test (PLT), as one of the partially destructive testing methods, includes two concentrated point loads applied to the lateral surface of the core specimen.…”
Section: Introductionmentioning
confidence: 99%
“…The overuse of natural aggregate in the construction sector has harmed the environment in recent decades, and it is estimated that about 7.5 billion tonnes of aggregates are annually consumed by the concrete industry [1][2][3][4][5]. This environmental issue can be somewhat solved by partial replacement of natural aggregates with artificial lightweight aggregates in the building process [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The use of recycled aggregate in concrete has been shown to lead to a decrease in the construction cost and it can reduce the burden on the environment by saving natural aggregates. 4 The abstract roller-compacted concrete (RCC) is a zero slump concrete comprising the same materials as that of conventional Discussion on this paper must be submitted within two months of the print publication. The discussion will then be published in print, along with the authors' closure, if any, approximately nine months after the print publication.…”
Section: Introductionmentioning
confidence: 99%